Kebutuhan Tipe Hunian Berdasarkan Umur Dan Status Kepala Keluarga - Yulinda Rosa (Jurnal Permukiman, 2016)
The availability of tendency information was selected by the type of dwelling households based on increasing age and sosial status, economic and cultural families, better known by dwelling type propensities very helpful to solve the problem of housing. Getting an idea of dwelling type propensities in Indonesia, conducted a case study in Depok, Cirebon and Pekanbaru with the technique of taking multistage sampling was taken in 1200 families, used a software program excel and Statistical Package Special Sciences (SPSS) to analyzes all faktors, regression analysis and descriptive analysis. The career of housing in all three samples of the city's most visible change in the age range ≤ 34 years, in line with the magnitude of changes in family income towards the more established and increase the number of families, accompanied by changes in the ownership of dwellings to change the size of the floor area toward larger, the highest achievement in the primary age range of 40 years of age 45 years. On average people in Depok work at the age of 22 years with an average senior high school, taking dwellings with contract status, average income of Rp. 1.3885 million, - (under MSE = Rp. 1,453,875, -). The average of  age almost 23 years began to be separated from their parents and live independently, the average income of Rp. 1.613 million, - inhabit the house with residential status contracting (0.25%) and 0.08% belongs to take the house status. The percentage of families take a house belonging to a sharp rise began when school-age children up to 55 years (69.23%) and tend to take a permanent dwelling place in  one location.